Formation of a Malin 1 analogue in IllustrisTNG by stimulated accretion - Zhu, Qirong; Zjupa, Jolanta; Springel, Volker; Pakmor, Rüdiger; Pillepich, Annalisa (Monthly notices of the Royal Astronomical Society. Letters, 2018)
ABSTRACT. The galaxy Malin 1 contains the largest stellar disc known but the formation mechanism of this structure has been elusive. In this paper, we report a